Psychometric properties of the Questionnaire of Myths about Giftedness in the Colombian population (2022)
INTRODUCTION: The present work shows the adaptation process and psychometric properties study of the Questionnaire of myths about Giftedness in the Colombian population. The initial version of the questionnaire consisted of a dichotomous scale of 20 items structured in four dimensions. METHOD: Two descriptive quantitative studies were carried out using a cross-sectional survey methodology. The questionnaire was applied at first to a sample of 160 teachers; and in a second moment, 424 teachers from public and private educational institutions from different regions of Colombia. The data were subjected to a study of internal consistency and the factorial structure by means of exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). RESULTS: The results obtained in the EFA made it possible to reduce the questionnaire to 18 items, maintaining four dimensions, which were tested using the CFA. The final version of the instrument was made up of 15 items and three dimensions: Myths related to the profile of giftedness and achievements; Myths related to social adaptation and physical aspects; and Myths related to the nature of giftedness. DISCUSSION: The three-dimensional model is appropriate with high goodness-of-fit indices and high reliabilities in all three dimensions and full scale. This questionnaire is a reliable tool for the assessment of false beliefs about giftedness in Colombian teachers.